2014
DOI: 10.1007/s10653-014-9655-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes of vector borne diseases with wetland characteristics using multivariate analysis

Abstract: Vector borne diseases are a threat to human health. Little attention has been paid to the prevention of these diseases. We attempted to identify the significant wetland characteristics associated with the spread of chikungunya, dengue fever and malaria in Kerala, a tropical region of South West India using multivariate analyses (hierarchical cluster analysis, factor analysis and multiple regression). High/medium turbid coastal lagoons and inland water-logged wetlands with aquatic vegetation have significant ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In addition, hierarchical cluster analysis was employed to group and classify wetland characteristics using JMP software from SAS (version 13). Cluster analysis can divide objects (e.g., wetlands) into different subgroups in such a way that objects in the same group are more similar with each other than with those in other groups (Richarme, 2002;Sheela et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hierarchical cluster analysis was employed to group and classify wetland characteristics using JMP software from SAS (version 13). Cluster analysis can divide objects (e.g., wetlands) into different subgroups in such a way that objects in the same group are more similar with each other than with those in other groups (Richarme, 2002;Sheela et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Such variations have been reported by other studies that used MaxEnt (36, 37). This is because although the mosquito species share similar habitats, their ecological requirements may show significant variation in terms of water quality (38, 39) and vegetation type (40). Other studies have also indicated that temperature and rainfall derivatives are the most influential predictors of mosquito distribution (24, 27, 41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the relationship between environmental variables and disease outbreaks (Franklinos et al, 2019; Hess et al, 2018; Semenza & Suk, 2018; Sheela et al, 2015). These investigations highlight that factors such as vegetation, hydrology, and physiography are strongly linked to vector habitat and disease outbreaks.…”
Section: Methodsmentioning
confidence: 99%